The quadratic form of spin-3 Lagrangian in the momentum space is: (Kn)ν1ν2ν3μ1μ2μ3=δ(ν1(μ1δν2μ2δν3)μ3)+6g(μ1μ2g(ν1ν2δν3)μ3)(−12+λβ2)+3(−1+λ)n(μ1n(ν1δν2μ2δν3)μ3)+6(12+λβ)(n(μ1nμ2g(ν1ν2δν3)μ3)+n(ν1nν2g(μ1μ2δν3)μ3))+6(−14+λβ2)n(μ1gμ2μ3)n(ν1gν2ν3)
where nμ is a momentum. The equation for the propagator is: (Kn)ν1ν2ν3μ1μ2μ3(Kn)−1μ1μ2μ3α1α2α3=δ(ν1(α1δν2α2δν3)(α3).
The following Redberry code produces propagator in four dimensions (here we used l
for λ and b
for β):
//quadratic form def K = ''' d^a_p*d^b_q*d^c_r + 6*g_pq*g^ab*d^c_r*(-1/2 + l*b**2) + 3*(-1 + l)*n_p*n^a*d^b_q*d^c_r + 6*(1/2 + l*b)*(n_p*n_q*g^ab*d^c_r + n^a*n^b*g_pq*d^c_r) + 6*(-1/4+l*b**2)*n_p*g_qr*n^a*g^bc '''.t //symmetrize upper indices def upper = K.indices.upper.si upper.symmetries.setSymmetric() K = Symmetrize[upper] >> K //symmetrize lower indices def lower = K.indices.lower.si lower.symmetries.setSymmetric() K = Symmetrize[lower] >> K //propagator addSymmetries 'P^{abc}_{mnk}', [[0, 1]].p, [[0, 1, 2]].p, [[3, 4]].p, [[3, 4, 5]].p // l.h.s of the equation def lhs = 'K^abc_mnk*P^mnk_pqr'.t lhs = "K^abc_pqr = $K".t >> lhs //r.h.s. of the equation def rhs = 'd^a_p*d^b_q*d^c_r'.t rhs = (Symmetrize[upper] & Symmetrize[lower]) >> rhs def options = [Transformations: 'd_n^n = 4'.t & 'n_a*n^a = 1'.t, ExternalSolver : [ Solver: 'Mathematica', Path : '/Applications/Mathematica.app/Contents/MacOS']] def s = Reduce(["$lhs = $rhs".t], ['P^{abc}_{pqr}'], options) println sHere we assumed n2=1, but the correct dimension can be easily recovered.
The produced result is rather huge. It can be written in the following form: (Kn)−1α1α2α3β1β2β3=Sym[c0nβ1nβ2nβ3nα1nα2nα3+c1δα1β1nβ2nβ3nα2nα3+c2δα1β1δα2β2nβ3nα3++c3δα1β1δα2β2δα3β3+c4gα1α2nβ1nβ2nβ3nα3+c5gα1α2δα3β1nβ2nβ3+c6gβ1β2nβ3nα1nα2nα3++c7gβ1β2δα1β3nα2nα3+c8gβ1β2gα1α2nβ3nα3+c9gβ1β2gα1α2δα3β3], Where Sym is a symmetrisation over upper and lower indices (as in the quadratic form) and the coefficients are: c0=20b2+4b−14(b+1)2+16(1+6b+6b2)2(12lb2−24b2−36b+12lb−14+3l)(7+12b2+18b)++3(4b2+10b+5)(2b+1)22l(b+1)2(7+12b2+18b)c1=−34(2b+1)(2lb+4b+6−3l)(b+1)2lc2=−3−1+llc3=1c4=−342b+1b+1−6(4b+3)(1+6b+6b2)(2b+1)(12lb2−24b2−36b+12lb−14+3l)(7+12b2+18b)++6(b+1)(2b+1)l(7+12b2+18b)c5=342b+1b+1c6=c4c7=c5c8=148−6l+3l2l(l−2)+1224lb+15l+2(l−2)(12lb2−24b2−36b+12lb−14+3l)lc9=−34